DOI: 10.17760/d20270204
|View full text |Cite
|
Sign up to set email alerts
|

Vermont school district consolidation case study

Abstract: Facing a declining K-12 student population and rising education costs, Vermont lawmakers approved Act 46 in 2015. This legislation has the potential to consolidate school districts that have fewer than 900 students. The law aims to significantly reduce the number of districts in the state by using tax incentives as a carrot and forced consolidation as a stick. Advocates of the legislation claim economies of size and scale will save Vermont taxpayers money and provide more educational equity for students. Oppon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Conceptual content analysis entails the identification of key words, terms, or phrases which provide narrative threads illustrating how broader concepts or themes are expressed and considered in communications and discourse (Elo and Kyngas 2008). It is similar to thematic analysis, which is often used in the study of stakeholder attitudes in school consolidation debates (Alberghini 2017; Nitta et al 2010; Post and Stambach 1999; Surface 2011). Content analysis differs in that it is a qualitative research method assisted by quantitative data management and analysis (Vaismoradi, Turunen, and Bondas 2013).…”
Section: Data Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conceptual content analysis entails the identification of key words, terms, or phrases which provide narrative threads illustrating how broader concepts or themes are expressed and considered in communications and discourse (Elo and Kyngas 2008). It is similar to thematic analysis, which is often used in the study of stakeholder attitudes in school consolidation debates (Alberghini 2017; Nitta et al 2010; Post and Stambach 1999; Surface 2011). Content analysis differs in that it is a qualitative research method assisted by quantitative data management and analysis (Vaismoradi, Turunen, and Bondas 2013).…”
Section: Data Methods and Resultsmentioning
confidence: 99%
“…The rationale for rural school consolidation regularly turns on issues of finances that couch the need for change in near deterministic reasons, such as declining tax bases necessitating consolidation and economies of scale dictating the need for more efficient administration (Bard et al 2006). Case studies of school consolidation experiences have found financial concerns to be a common theme (Alberghini 2017; Post and Stambach 1999). Those who study risk, hazard, and adaptation also note how economic considerations can drive action, or inaction, and can be contested (Cutter et al 2008).…”
Section: Data Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation